Transforming humanitarian logistics: the journey to supply network management - Tatham, Peter (Henry Stewart Talks, 2012)
Definitions of a disaster, Disaster frequency and impact, Non-government organizations (NGOs), definitions and roles, Key challenges, Needs assessment, Funding, coordination, Metrics, Organizational learning, 2005 Pakistan earthquake, Bangladesh cyclones